Statistics for analytical chemistry - Miller J C; Miller, J N. (New York Ellis Horwood PTR Prentice Hall, 1993)
This third edition gives a clear and lucid account of the underlying principles of statistical methods. It reflects the enormous impact of microelectronics for the rapid calculation of chemometric procedures such as pattern recognition, optimization and numerical techniques." "Significant changes and updates to most chapters of the previous edition have been made, particularly in curvilinear regression methods, robust statistical methods, multivariate methods, outliers in univariate statistics and calibration methods, initial data analysis, and experimental design and optimization. Fully revised bibliographies are included at the end of each chapter, together with exercises and solutions." "Readership: Researchers and laboratory workers, including professional scientists in all areas of analytical chemistry. Undergraduate and postgraduate students of analytical chemistry, and their teachers.
Keywords: Analytical Chemistry